2012
DOI: 10.1021/jf303516w
|View full text |Cite
|
Sign up to set email alerts
|

Solophenols B–D and Solomonin: New Prenylated Polyphenols Isolated from Propolis Collected from The Solomon Islands and Their Antibacterial Activity.

Abstract: Three new prenylated flavonoids, namely, solophenols B (1), C (2), and D (3), as well as a new prenylated stilbene, solomonin (4), were isolated from propolis collected from the Solomon Islands. In addition, 17 known compounds were identified. The structures of the new compounds were determined by a combination of methods, including mass spectrometry and NMR. These new compounds and several known compounds were tested for antibacterial activity against Staphylococcus aureus, Bacillus subtilis, and Pseudomonas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 22 publications
2
24
0
Order By: Relevance
“…Thus, this type of propolis from the Pacific region are called 'Pacific propolis' [1]. Further we isolated some prenylflavonoids from the Solomon Islands and Hawaii identical to those found from Okinawan propolis [9,10]. These findings indicate that the propolis from the Solomon Islands and Hawaii have the same botanical origin, M. Tanarius, as Okinawan propolis.…”
Section: -2supporting
confidence: 57%
“…Thus, this type of propolis from the Pacific region are called 'Pacific propolis' [1]. Further we isolated some prenylflavonoids from the Solomon Islands and Hawaii identical to those found from Okinawan propolis [9,10]. These findings indicate that the propolis from the Solomon Islands and Hawaii have the same botanical origin, M. Tanarius, as Okinawan propolis.…”
Section: -2supporting
confidence: 57%
“…Prenylated flavanone-type compounds, which were previously classified as a chemical marker of Pacific HBP, have been found not only in Asia (Japan [ 75 , 85 ], Oman [ 125 ], and Taiwan [ 70 , 84 ]), and Oceania (Fiji [ 143 ] and Solomon Island [ 106 , 117 , 118 ]), but also in Africa (Egypt [ 92 , 100 ] and Nigeria [ 141 ]). These compounds originated from Macaranga spp.…”
Section: Propolis Components: Chemistry and Geographical Distributmentioning
confidence: 99%
“…In the past few years, prenylated quercetin analogs, such as solophenol D and uralenol, have gained a lot of attention due to their antibacterial properties. It has been reported that prenylation may enhance the biological functions of quercetin by increasing its hydrophobicity and bioavailability [ 23 , 24 ].…”
Section: Chemistry Of Quercetin and Its Analogsmentioning
confidence: 99%